Profile of Electronic and Digital Media Learning Implementation During 2018-2022 - Dinda Habba Kamaliya; Tukiran; Sifak Indana (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2022)
This research aims to describe and analyze the implementation of digital and electronic media as learning media during the COVID-19 pandemic. This research is a qualitative research using a literacy study method based on articles and books relevant to the implementation of digital and electronic learning media in Indonesia in the period 2018-2022. As for analyzing research data, the author uses inductive thinking methods. This method brings together various information from previous research related to the use of digital and electronic media as learning media during the COVID-19 pandemic. to be generalized into a new idea whose validity can be justified. Based on the results of a study of 20 articles from previous research, it can be seen that research on digital and electronic media as learning media in 2018-2022 contains development and application during the Covid-19 pandemic. The types and methods of research carried out varied including research and development, qualitative, quantitative, and literature review research. The development and application of digital and electronic media has proven to be still not fully effective in the learning process during this pandemic, the difficulty of internet access is still an obstacle for several studies. However, there are also many studies that show that the use of digital and electronic media in the learning process is considered effective, interesting and easily accessible to students wherever and whenever.